Malignant lymphoma in congenital dyserythropoietic anaemia type III. - McCluggage, W G (1996)
A 60 year old woman with congenital dyserythropoietic anaemia (CDA) type III developed a malignant T cell lymphoma with cutaneous and widespread nodal involvement. Bone marrow aspirates showed erythroid hyperplasia and dyserythropoiesis with multinucleate erythroblasts and gigantoblasts, in keeping with CDA type III. Electron microscopy showed multinucleate erythroblasts with notably irregular nuclear outlines and intranuclear clefts. The development of malignant lymphoma in this patient, together with a documented high prevalence of monoclonal gammopathy and multiple myeloma and a single case of Hodgkin's disease, may indicate an increased incidence of lymphoproliferative disease in CDA type III.